2021
DOI: 10.3390/math9182279
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Nature-Inspired Algorithms for Long-Term Digital Preservation

Abstract: Digital preservation is a research area devoted to keeping digital assets preserved and usable for many years. Out of the many approaches to digital preservation, the present research article follows a new object-centered digital preservation paradigm where digital objects share part of the responsibility for preservation: they can move, replicate, and evolve to a higher-quality format inside a digital ecosystem. In the new framework, the behavior of digital objects needs to be modeled in order to obtain the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Digital objects are mainly files and, if they are programmed with the mission to persist and remain accessible, their strategy to do so is achieved by requesting preservation services spread among the Internet in order to guarantee the quality of their main defining attributes-accessibility, readability, integrity and authenticity-over time. In [15], the final simulated results obtained demonstrated that a digital preservation environment with objects programmed for self-preservation is possible. The experiments presented there were a first step towards creating real structured environments where models coexist under a predefined system of rules and constraints and concluded that more tests were needed in order to characterize the desirable properties that could be required from intelligent behaviors, the distributed interaction environment and the response of the The results presented in the current work follow the opened path and add a new constrain to DO behavior inside the DP paradigm initially proposed.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Digital objects are mainly files and, if they are programmed with the mission to persist and remain accessible, their strategy to do so is achieved by requesting preservation services spread among the Internet in order to guarantee the quality of their main defining attributes-accessibility, readability, integrity and authenticity-over time. In [15], the final simulated results obtained demonstrated that a digital preservation environment with objects programmed for self-preservation is possible. The experiments presented there were a first step towards creating real structured environments where models coexist under a predefined system of rules and constraints and concluded that more tests were needed in order to characterize the desirable properties that could be required from intelligent behaviors, the distributed interaction environment and the response of the The results presented in the current work follow the opened path and add a new constrain to DO behavior inside the DP paradigm initially proposed.…”
Section: Discussionmentioning
confidence: 94%
“…The objective of this research document is to present new results obtained as a continuation of the work published in [15]. That previous publication contained a proposal for a novel object-centered paradigm to address the digital preservation problem where digital objects, programmed with using basic computational intelligence behaviors, shared part of the responsibility for self-preservation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations